Quality of Eugenia involucrata seeds: a physiological and biochemical approach as a response to fruit maturation - Costella, Claudia; Gasparin, Ezequiel; Machado-Araujo, Maristela; Griebeler, Adriana Maria; Miranda-Aguilar, Marcos Vinicius; Silva-Wertonge, Gerâne; Caroline Castro-Kuinchtner, Caroline; Souza, Hendrick; Pegoraro-Stangarlin, Mauricio; Cezimbra-Quevedo, Alexsandra (BOSQUE, 2025)
Most native species in Brazil have knowledge gaps regarding seed and seedling production and ecological restoration. Eugenia involucrata is a species of great ecological, medicinal, and commercial value, with seeds being the primary method of propagation, despite the difficulty in selecting trees and collecting and conserving recalcitrant seeds. The objective of this study was to understand the effects of fruit maturation on seed germination and storage. Based on the classification of fruits into three maturation stages (red–yellow: RY = 7.5YR 7/10; red: R = 10R 4/10; and purple: P = 5R 3/4) characterized by the Munsell Color System, we analyzed: a) the biometrics of fruits and seeds; b) biochemical aspects (hydrogen peroxide (H2O2), superoxide dismutase (SOD), and guaiacol peroxidase (POD)); c) physiological (pre-germination treatments and seed storage); and d) physical and sanitized seed quality. We found that germination was slow, occurring for approximately 60 days, and could not be improved by the pre-germination treatment. R fruits suffered fewer H2O2 reactions, which was related to increased SOD and POD antioxidant activity, whereas RY and P fruits were associated with higher H2O2 concentrations. After storage (60 d), the seed water content did not decrease significantly, regardless of fruit color; however, R fruit seeds were less affected by fungi of the genera Aspergillus sp. and Cladosporium sp. R fruits are important morphological markers for collection, extending the duration of seed usage when stored in a cold and humid chamber, whereas seeds extracted from P fruits must be sown immediately to avoid a 25 % reduction in germination in just two months of storage.